Rediscovering God in America : reflections on the role of faith in our nation's history and future - Gingrich, Newt. (Nashville : Integrity House, 2006)
"Significant monuments, memorials, and artifacts found in our Nation's capital are Creator-endowed as seen through a walk through tour of Washington DC"--Provided by publisher.
Introduction : The creator and the American public square -- The National Archives -- The Washington Monument -- The Jefferson Memorial -- The Lincoln Memorial -- Vietnam Veterans Memorial -- The Franklin Delano Roosevelt Memorial -- The U.S. Capitol building -- The U.S. Supreme Court -- The Library of Congress -- The Ronald Reagan building -- The White House -- The World War II Memorial -- Arlington National Cemetery -- Conclusion : Laus Deo -- A walking tour of our nation's capitol. Directions and map. Selected images on your tour.
Keywords: Rediscovering God -- America; Washington (D.C.) -- Religion; Washington (D.C.) -- Buildings, structures, etc; Washington (D.C.) -- Description and travel